Income Distribution of Informal Sector Labor in Indonesia 2022 - Sari, Bellia Mega; Sugiarto (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2024)
Purpose This research aims to look at the description of the characteristics and factors that influence the categories of income levels under class (vulnerable and poor) and aspiring middle class in informal sector labor in Indonesia 2022. Design/methodology/approach The dataset from raw data of the National Labor Survey (SAKERNAS) in February 2022 collected by Badan Pusat Statistik (BPS). This research used the ordinal logistic regression, model of partial proportional odds (PPOM). The dependent variable used is the income level category based on the classification determined by World Bank. Findings This research finds that 58 percent of the population are informal labor. The results of the analysis show that the level of education, job training, work experience, type of work, age, gender, marital status, working hours, and residential area classification have a significant effect on income level categories. Research limitations/implications This research only includes sample of informal sector labor who have income and based on the main job status classification from BPS. Originality/value In this research, income of informal sector labor are categorized based on classification determined by World Bank. Then there has not been much research on the characteristics of informal sector labor and what influences the level of their income category.